Developing countries in the international economy : selected papers - Lall, Sanjaya (London ; Atlantic Highlands, N.J. : Macmillan ; Distributed in the U.S.A. by Humanities Press, 1981)
'... a most stimulating essay, by an economist who is a leading authority in his field ... a most welcome addition to the literature on economic development.' Terence J.Byres, British Book News '... a perceptive and challenging contribution to the economics of technology transfer and industrialization.' Michael Hobday, The Economic Journal.
Distributor statement from label mounted on t.p.
Includes bibliographical references and index.
rpm 14/11/2017
Loans
Keywords: Economic assistance; Economic development; Developing countries